Islamic Spiritual Organizations as Moderation-Oriented Civic Learning Spaces: Preventing Radicalization in an Indonesian Public Senior Secondary School - Alfarisi, Muhammad Salman; Yahuda, M.; Saputra, Edi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Islamic Spiritual Organizations (Rohis) in Indonesian public schools occupy a dual position: they can either reproduce exclusive religious narratives or become co-curricular spaces for moderation, critical literacy, and civic learning. This qualitative descriptive case study examines how Rohis at State Senior High School 4 of Jambi City functions as a preventive educational space. Data were generated over one semester through non-participant observation, semi-structured interviews with 12 purposively selected informants, and documentary analysis. The findings identify four mutually reinforcing mechanisms: moderation-centred religious study, dialogical mentoring, digital counter-narratives, and cross-class social action. School monitoring records also show more active discussion participation (60% to 80%) and higher descriptive tolerance scores among active Rohis members than inactive students (8.4 versus 5.7 on a 10-point rubric). These indicators are interpreted as contextual evidence rather than causal estimates. The study contributes a moderation-oriented civic learning model that positions Rohis as an inclusive pedagogical infrastructure aligned with quality education and peacebuilding. Its effectiveness, however, depends on teacher supervision, transparent learning materials, inclusive recruitment, and programming that reaches students beyond the organization.